The Industrial Workers of the World and the Unemployed in Edmonton and Calgary in the Depression of 1913-1915 - Schulze, David (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1990)
Abstract The radicalism of the Industrial Workers of the World (IWW) in the early 20th century placed it outside of the dominant, contemporary social ideology. At the same time, there were large numbers of unskilled, migrant, and largely immigrant workers employed in seasonal, labour-intensive industries, whose social and economic marginalization made them receptive to the IWW's radicalism, while the IWW was prepared for the radical step of attempting to organize them. This paper is a study of the IWW's efforts to organize the unemployed of Edmonton and Calgary during the depression of 1913-1915: most were transient and unskilled; many had just arrived from railway construction camps in the interior where the IWW had led massive strikes. The tactics used in the struggle included large demonstrations, the invasion of churches, and refusals to pay for restaurant meals. But the special nature of unemployment — which was caused by the economic system, threatened the men's integrity as workers, but was dealt with by the State — allows a careful examination of the practical effects of the IWW's ideology. Other Canadian cities saw protests by the unemployed, but only the IWW in Alberta asked for work at the best going rate for general labour, 30 cents an hour, and if they could not get that they demanded free food and accommodation. They tried to preserve the men's integrity as labourers, based on a belief that unemployment was not an inevitable experience to be passively endured, but a nefarious consequence of capitalism to be actively resisted. The IWW also fostered an inter-ethnic solidarity founded on a right to work, "regardless of race, color or nationality." However, the IWW's efforts also took place within very narrowly circumscribed limits: the workers they represented had little economic bargaining power and less still in a time of unemployment, when they were dependent on urban political authorities to whom most had no other connection. Their political force was only equal to their threat to public order and hungry men were no match for the police. Moreover, responsibility for their relief was thrust onto municipalities which could barely afford to care for the resident unemployed. In the end, the difficulty of achieving even short-term material gains must have discouraged most workers and doomed the organization to instability.